Concepts of firmness and balancing in marketing logistics - Garasym, P.; Gerasymenko, O.; Garasym, M. (Publishing House of Lviv Polytechnic National University, 2015)
Concepts of firmness and balancing are considered. Place of firmness and balancing in marketing logistics is defined. The authors have come to the conclusion that the system which is considered stable for any moment is not necessarily simultaneously balanced. According to the integrated continuum of logistics development intensity and marketing concepts balancing of marketing logistics have a place in social and ethical marketing concept. Firmness of marketing logistics can be observed in any point of continuum if situation is constant for a long time.
Keywords: marketing logistics; concepts; firmness; balancing; continuum